Issue of Adolescent Educational Needs on Reproductive Health in The Rural Area of Kulon Progo Yogyakarta: A Qualitative Study - Nisman, Wenny Artanty; Parmawati, Ika; Lismidiati, Wiwin; Mulyani, Sri; Warsini, Sri; Widyasari, Anis; Sumekar, Lintang Ayu; Jati, Puspa Silvia; Zulfa, Azizah Tiara; Suryani, Saltsa Rahmalia (Universitas Negeri Semarang, 2025)
Background: Adolescents in rural areas often face greater challenges with reproductive health problems than adolescents in urban areas, including more difficult access to health services, less access to reproductive health information, and limited social support. This affects the high prevalence of reproductive health problems such as teenage pregnancy, sexually transmitted infections (STIs), and limited understanding of sexual and reproductive health rights The objective of this study was to explore the educational needs The purpose of this study is to investigate more comprehensively the needs of adolescents about reproductive health education in rural areas of Kulon Progo, Yogyakarta. Method: This is a qualitative study with a phenomenological approach, and data collection methods with in-depth interviews. The research participants consisted of 10 adolescents who lived in a rural area and were analysed using thematic analysis. Result: Four major themes were found from the results of this research, among others: adolescents' experience of getting education about reproductive health, challenges faced by adolescents around reproductive health education, the most appropriate person to provide reproductive health education to adolescents, and the need for adolescent education on reproductive health. Conclusion: The challenges faced by adolescents living in rural areas regarding reproductive health education:Adolescents feel uncomfortable discussing reproductive health with their parents, but feel comfortable discussing it with their peers, even though they cannot help them. The internet is still the main source for asking questions about reproductive health, but often they do not get the right answers.